(untitled) (LEARNing Landscapes, 2012)
Though most educators understand that museums can be a useful resource, many seem unsure how to incorporate a visit into their teaching practice. The author uses his years of experience to explain how museums are creating educational activities in order to attract class trips. Examples from two history museums in Montreal are cited to show the variety of pedagogic activities available. The author concludes with advice for teachers who want their visit to succeed.